The concept of a contract of service and its application in Malaysia / Ani Solep - Solep, Ani (Faculty of Law, 1985)
The Concept of a contract of service and its application in Malaysia becomes a choice, for my project paper because it is an area of law that has aroused my interest. It is a perpetual wonder to me that after dealing with the contract of service concept for over a hundred years the court is left almost where it begun. Admittedly the statutes passed have been of some assistance but the mystery of the / contract of service concept lingers on. My objective therefore is to put in writing what the said concept is about together with rights, duties, obligations and liabilities that naturally arise from such a relationship. In the course of writi ng this project paper I have replied mostly on articles, textbooks and decided cases. The reason is that, I feel that the topic is almost purely of academic interest' and the layman have very scanty knowledge about it. I would like to thank Denny for suggesting the topic of this project paper and En Darby Hashim, Course Tutor Diploma In Law for making amendments to my original phrasing of the topic. My special thanks are due to my Supervisor, Mr Teh Hock Kee for his constructive criticislns and advice. I am also greatly indebted to my typist, Sharifah Fazilah Syed Agil who managed to complete typing the manuscripts on time although she was given a very short notice. Lastly I'would like to extend my appreciations to my cousin Julia Roning Minjat and my family for their moral and financial support.